Public Policy Formulation and Its Implications for Community Welfare in the Era of Regional Autonomy - Hikmat (AKADEMI TEKNIK ADI KARYA, 2025)
This study examines the dynamics of public policy formulation and its implications for community welfare within the context of regional autonomy in Indonesia. The decentralization framework grants local governments greater authority in designing, implementing, and evaluating policies that directly address local needs. However, variations in institutional capacity, leadership quality, stakeholder involvement, and fiscal management often lead to disparities in policy effectiveness. This research employs a qualitative literature review supported by policy analysis to identify key determinants that shape policy outcomes at the local level. The findings reveal that inclusive policy formulation—characterized by participatory decision-making, inter-agency collaboration, and evidence-based approaches significantly contributes to improving public welfare outcomes. Conversely, weaknesses in governance practices, such as limited transparency, low bureaucratic competence, and inadequate budget allocation, hinder policy impact and perpetuate regional inequality. The study underscores that effective policy formulation in the autonomy era requires strengthening institutional capacity, enhancing community engagement, and optimizing local fiscal resources. Ultimately, the research highlights that robust policy design has the potential to accelerate welfare improvement, reduce regional disparities, and support sustainable development at the local government level.